COLLABORATIVE GOVERNANCE DALAM PROGRAM KETAHANAN PANGAN DI KABUPATEN SUMEDANG - Suarha, Cecep; Triadi, Rahma; Saputra, Ginanjar Wira; Santosa, Pandji (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
Food security is a vital aspect of regional development, especially in disaster-prone areas such as Sumedang Regency. Food security programs require strategic collaboration between local government and security institutions to ensure effective food distribution and enhance community resilience. This study aims to analyze the implementation of collaborative governance in the food security program in Sumedang Regency, focusing on the role of Brimob Polri as a strategic partner of the local government. The research uses a qualitative descriptive approach with data collection techniques through in-depth interviews, field observations, and document analysis. Data are analyzed using Miles & Huberman's interactive model including data reduction, data display, and verification of conclusions. The research results show that collaborative governance has proceeded through three main stages: strategic planning, policy implementation, and monitoring-evaluation. Brimob Polri plays an important role in ensuring secure distribution, providing community education, and logistical support. However, challenges remain such as differences in institutional priorities, limited logistical infrastructure, the need to increase community participation, and geographic barriers. This research provides important contributions to understanding the mechanism of collaborative governance for food security in disaster-prone areas and offers strategic recommendations for optimizing cross-sector collaboration in the context of sustainable development and disaster risk reduction.